Exploring the factors that influence the decision to adopt and engage with an integrated assistive telehealth and telecare service in Cambridgeshire, UK: a nested qualitative study of patient 'users' and 'non-users'. Issue 1 (December 2016) - Cook, Erica; Randhawa, Gurch; Sharp, Chloe; Ali, Nasreen; Guppy, Andy; Barton, Garry; Bateman, Andrew; Crawford-White, Jane
Abstract Background There is a political drive in the UK to use assistive technologies such as telehealth and telecare as an innovative and efficient approach to healthcare delivery. However, the success of implementation of such services remains dependent on the ability to engage the wider population to adopt these services. It has been widely acknowledged that low acceptance of technology, forms a key barrier to adoption although findings been mixed. Further, it remains unclear what, if any barriers exist between patients and how these compare to those who have declined or withdrawn from using these technologies. This research aims to address this gap focusing on the UK based Cambridgeshire Community Services Assistive Telehealth and Telecare service, an integrated model of telehealth and telecare. Methods Qualitative semi-structured interviews were conducted between 1st February 2014 and 1st December 2014, to explore the views and experiences of 'users' and 'non-users' using this service. 'Users' were defined as patients who used the service (N  = 28) with 'non-users' defined as either referred patients who had declined the service before allocation (N  = 3) or had withdrawn after using the ATT service (N  = 9). Data were analysed using the Framework Method. Results This study revealed that there are a range of barriers and facilitators that impact on the decision to adopt and continue to engage with this type of service. Having a positive attitude and a perceived need that could be met by the ATT equipment were influential factors in the decision to adopt and engage in using the service. Engagement of the service centred on 'usability', 'usefulness of equipment', and 'threat to identity and independence'. Conclusions The paper described the influential role of referrers in decision-making and the need to engage with such agencies on a strategic level. The findings also revealed that reassurance from the onset was paramount to continued engagement, particularly in older patients who appeared to have more negative feelings towards technology. In addition, there is a clear need for continued product development and innovation to not only increase usability and functionality of equipment but also to motivate other sections of the population who could benefit from such services. Uncovering these factors has important policy implications in how services can improve access and patient support through the application of assistive technology which could in turn reduce unnecessary cost and burden on overstretched health services.